Computer Sciences Student Competency System (CSSCS) for Information Technology (CS220) students - Muhamad Shuaimi, Nurliyana (2013)
This research project is about developing an information system that can evaluate student‟s skills which can close the gap between industrial demands university supplies by mapping the computer sciences student‟s skills needed by industry and supply provided by the university with the job opportunities. By using the standards that UiTM already have and then comparing it with the market needs, the project will come out with the best competencies on how to measure the student‟s performance in industrial training. Generally, the percentage of unemployement of UiTM graduates was increasing especially Information Technology students. Most of the students have difficulties in getting job for about six month from their graduation day because they cannot find the job that meet their strength and ability. This research will be focused on developing the Computer Sciences Student Competency System (CSSCS) for Information Technology (CS220) which may help the supervisor to evaluate the technical skill from student for industrial training and the system also focuses on identifying the skills needed in industry and the criteria that the industry need from candidates in Science Computer field for particular job. By applying Rapid Application Development (RAD) as a method to conduct the system, it may ease the development of the system. On top of that, by having the major idea and concept of evaluation skills system, it is applicable to the Computer Sciences Student Competency System (CSSCS) which can be applied in others faculty or other university once this project success. The adapted class diagram will then contributes and assists the developers to build up a system after requiring that documentation of the design pattern. As the result, the Computer Sciences Student Competency System (CSSCS) will assist the supervisor from industry and also university to manage the data of student skill based on their requirements. This research will succeed phase by phase in order to achieve the aim of the project. Thus, the final outcome is, this system can close the gap and students may know what job that is suitable for their skills. Hopefully the system can be implement and apply at faculty and also others faculty in UiTM.